Post-Laminectomy Non-Osseous Intraspinal Extradural Tuberculous Granulation Tissue: An Undescribed Entity - Jeyaselva Senthilkumar Thotlampatti Pachiyappan; Sekar Chinnamuthu (Indian Journal of Neurosurgery)
Spinal tuberculosis (TB) is well studied and described in the literature. It is known to occur anywhere along the transverse plane of the spine. Vertebral TB accounts for less than 1% of all TB infections in the body and more than 50% of musculoskeletal infections. It is considered the most serious type of skeletal TB, with possible neurological symptoms due to compression of neural structures. It may also lead to deformity and significant vertebral structure destruction and instability. Though non-osseous intraspinal extradural tuberculous granulation tissue is reported in several instances, to the best of our knowledge and thorough literature search, the post-laminectomy occurrence of extradural tuberculous granuloma is not reported in the literature so far. Whether it is the reactivation of previously dormant tuberculous infection or naive infection is elusive. Surgical excision and anti-tuberculous therapy is the mainstay of treatment.